2.5-D multilayer optimisation of an industrial switchgear busbar system. (25th May 2016) - Bedkowski, M.; Smolka, J.; Bulinski, Z.; Ryfa, A.
Highlights: Optimisation of an industrial switchgear busbar system was conducted. The genetic algorithms with numerical solvers were combined to perform the overall design optimisation. The optimised design was verified by the two-way coupled CFD-EMAG model. Abstract: In this paper, a 2.5-D multilayer model was used to optimise an industrial switchgear busbar system using electromagnetic (EMAG) solutions. Moreover, the optimised design was verified by the two-way coupled CFD-EMAG model which included 3-D geometry. The 2.5-D multilayer approach allowed the robustness of the whole optimisation process to be increased, whereas the coupled EMAG-CFD computation provided the necessary information regarding the temperature field. The genetic algorithm was employed in the optimisation procedure to simultaneously minimise the conductors' cross-section area and the power losses. Therefore, to obtain the unique solution, two objective functions (OFs) with different weights were used. Then the optimised cross-sections from the 2.5-D model were translated into a 3-D busbar system to verify the final temperature for the new design. As a result of the study the new busbar system was proposed. In comparison to the initial design, the copper weight was reduced by 4.5%, whereas the average busbar temperature increase was only 2 to 3 K.